IN VIVO EFFICACY OF ORAL AND INTRAPERITONEAL ADMINISTRATION OF EXTRACTS OF WARBURGIA UGANDENSIS (CANELLACEAE) IN EXPERIMENTAL TREATMENT OF OLD WORLD CUTANEOUS LEISHMANIASIS CAUSED BY LEISHMANIA MAJOR. - Ngure, P. K.; Ng’ang’a, Z.; Ingonga, J.; Rukunga, G.; Tonui, W. K. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
The antileishmanial activity of extracts of Warburgia ugandensis Spraque (Canellaceae), a known traditional therapy in Kenya was evaluated in vivo. Treatment of infected BALB/c mice with W. ugandensis extracts orally resulted in a reduction of the size of lesions compared to the untreated control. The lesion sizes differed significantly for the four extracts (p=0.039) compared to the untreated control. For mice treated by intraperitoneal injection, the lesion sizes increased initially for the hexane, dichloromethane and ethyl acetate extracts and healed by day 42. The lesion sizes for mice treated with methanol increased steadily from 2.47mm to 3.57mm. The parasitic burden was significantly higher (p<0.001) in mice treated with methanol extracts and PBS compared to those treated with hexane, dichloromethane and ethyl acetate. This study demonstrated the antileishmanial potential of extracts of W. ugandensis.